1955
DOI: 10.1017/s0021859600039903
|View full text |Cite
|
Sign up to set email alerts
|

The storage of ware potatoes in permanent buildings II. The temperature of unventilated stacks of potatoes

Abstract: 1. Under normal English storage conditions, the heat production of mature potatoes drops rapidly from a value of probably about 150 b.th.u./ton/hr. immediately after harvest to about 30–50 b.th.u./ton/hr. Sprouting is accompanied by an increase in the rate of heat production. The initial heat production of immature potatoes may be of the order of 250 b.th.u./ton/hr.2. As a result of the production of heat, the temperatures in stacks of potatoes will tend to rise to levels above that of the outside air which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1956
1956
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The effect of bulk porosity in the range of 0.3-0.4 (particularly 0.35-0.4) is of commercial interest as because, the potatoes in bag or bulk have bulk porosity of the order of 0.4 (Burton, Mann, & Wager, 1955;Xu, Burfoot, & Huxtable, 2002). When the bags of potatoes are placed one above another in the form of a stack, the bags near the bottom end compressed due to the load of the upper bags and hence the porosity in the lower bags decrease.…”
Section: Effect Of Bulk Medium Porositymentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of bulk porosity in the range of 0.3-0.4 (particularly 0.35-0.4) is of commercial interest as because, the potatoes in bag or bulk have bulk porosity of the order of 0.4 (Burton, Mann, & Wager, 1955;Xu, Burfoot, & Huxtable, 2002). When the bags of potatoes are placed one above another in the form of a stack, the bags near the bottom end compressed due to the load of the upper bags and hence the porosity in the lower bags decrease.…”
Section: Effect Of Bulk Medium Porositymentioning
confidence: 99%
“…(Chourasia & Goswami, 2001). It is reported that the rate of metabolic heat production from the immature potatoes could be about 80 W/m 3 at 10°C (as high as 110 W/m 3 at 22°C) in comparison to 48 W/m 3 from mature tubers at the same temperature (Burton et al, 1955). However, during the storage period the normal range varies from 10 to 16 W/m 3 .…”
Section: Effect Of Metabolic Heat Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Treadway et al (1949) found that the sprouts were higher in reducing sugars and lower in starch than the whole tuber, and Mondy and Mattick (1969) observed that sprouts contained significantly more crude lipid and phospholipid than either the cortex or pith sections of the tuber. Sprouting is associated with increased respiration (Burton et al 1955) and amylase activity (Bruinsma 1962). Although Cotrufo (1958) found no large changes in amino acid content of the internal tissues of potatoes at the breaking of the rest period, Ashford and Levitt (1965) observed that the proteinhonprotein nitrogen ratio was higher in the cortex than in the pith tissue both at 3°C and at 26OC storage.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the carbon dioxide production has been measured (Burton et al, 1955;Burton, 1966;Hunter, 1976). Many of the determinations have been carried out in laboratories.…”
Section: Introductionmentioning
confidence: 99%